Infectious Bronchitis (IB) Disease and its Control in Chicken - Indriani, Risa; ., Darminto (Indonesian Animal Sciences Society, 1999)
Infectious Bronchitis (IB) is an acute, highly contagious viral respiratory disease of chickenâs caracterized by tracheal rallies, coughing, sneezing and nasal discharge in young chicks. In addition, the disease may affect kidhney, and in laying flock there is usually a drop in egg production and quality. IB is a major negative economic importance in poultry industry because the disease causes poor weight gain and feed efficiency, mortality in young chicks, reduction in egg production and egg quality in laying flock. IB is distributed worldwide and has been reported to be present in Indonesia. IB is caused by virus of a member of Coronaviridae under genera of Coronavirus. Spreading of IB virus among chickens usually by inhalation. Diagnosis of the disease can be based on the isolation and identification of the virus using embryonated chicken eggs and trachea organ culture. There is no treatment available for IB, so the control of the disease is mainly by vaccination. The existence of multiple serotipes of IB virus requires vaccines which are represent the antigenic spectrum of field isolates. To ensure the results of vaccination program, monitoring antibody titers following vaccination is recommended. The most widely used serological test for antibody monitoring is an enzyme linked immunosorbent assay (ELISA) or Haemaglutination Inhibition (HI) test. Â Key words: IB, virus, chicken, control